Septin clearance from the division site triggers cytokinesis in budding yeast - Davide Tamborrini; Simonetta Piatti (Microbial Cell)
In many eukaryotic cells cytokinesis involves a contractile actomyosin ring (CAR) that drives cleavage furrow ingression. What triggers CAR constriction at a precise time of the cell cycle and how constriction is coupled to chromosome segregation are fundamental questions. In the budding yeast Saccharomyces cerevisiae, CAR assembly strictly requires a rigid septin collar that forms at the bud neck early during the cell cycle. At the time of cytokinesis, a sudden remodelling of the septin collar occurs, leading to its splitting into two separate rings that sandwich the CAR. We have shown that septin displacement during splitting is an essential prerequisite for CAR constriction [Tamborrini et al., Nat Commun. 9(1):4308]. Thus, cytokinesis in budding yeast is a two-step mechanism: during the first step, the septin collar organizes the assembly of the cytokinetic machinery at the right place while restraining CAR-driven membrane ingression; during the second step, a confined eviction of septins from the division site during septin ring splitting triggers CAR constriction. Our data further indicate that septin ring splitting is prompted by the Mitotic Exit Network (MEN), and in particular by its downstream phosphatase Cdc14, independently of its mitotic exit function. Surprisingly, MEN signalling at spindle pole bodies (SPBs) is critical for septin ring splitting and cytokinesis. Ubiquitination of the MEN anchor at SPBs by the Dma1/2 ubiquitin ligase attenuates MEN signalling and could have a decisive role in coupling cytokinesis to chromosome and organelle segregation. Altogether, our data emphasize the importance of septin ring splitting, which has been mysterious so far, and highlight a novel mechanism to prevent CAR constriction and cytokinesis in unpropitious conditions.